2014
DOI: 10.1371/journal.pone.0114459
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Mitochondrial Genotoxins and Dopaminergic Neurodegeneration in Caenorhabditis elegans

Abstract: Neurodegeneration has been correlated with mitochondrial DNA (mtDNA) damage and exposure to environmental toxins, but causation is unclear. We investigated the ability of several known environmental genotoxins and neurotoxins to cause mtDNA damage, mtDNA depletion, and neurodegeneration in Caenorhabditis elegans. We found that paraquat, cadmium chloride and aflatoxin B1 caused more mitochondrial than nuclear DNA damage, and paraquat and aflatoxin B1 also caused dopaminergic neurodegeneration. 6-hydroxydopamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2
2

Relationship

3
7

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 119 publications
4
49
0
Order By: Relevance
“…However, UVC-induced mtDNA damage only caused larval growth arrest in fusion ( fzo-1, eat-3 )-deficient nematodes, suggesting that individuals with fusion deficiencies are more susceptible to toxicity induced by irreparable mtDNA damage. In agreement with this, we have also observed sensitivity to the mycotoxin aflatoxin B 1 and the chemotherapeutic cisplatin, both of which can cause irreparable mtDNA damage (González-Hunt et al 2014; Niranjan et al 1982; Podratz et al 2011), in fzo-1 - and eat-3 -deficient but not drp-1 C. elegans (Luz et al 2017). Although the precise reason for sensitivity to irreparable mtDNA damage in fusion-deficient C. elegans remains unknown, one possibility is the existence of a threshold effect in which >65% of mtDNA must typically be damaged or lost prior to pathogenesis (Taylor and Turnbull 2005).…”
Section: Gene-environment Interactions: How Does Genetic Variationsupporting
confidence: 87%
“…However, UVC-induced mtDNA damage only caused larval growth arrest in fusion ( fzo-1, eat-3 )-deficient nematodes, suggesting that individuals with fusion deficiencies are more susceptible to toxicity induced by irreparable mtDNA damage. In agreement with this, we have also observed sensitivity to the mycotoxin aflatoxin B 1 and the chemotherapeutic cisplatin, both of which can cause irreparable mtDNA damage (González-Hunt et al 2014; Niranjan et al 1982; Podratz et al 2011), in fzo-1 - and eat-3 -deficient but not drp-1 C. elegans (Luz et al 2017). Although the precise reason for sensitivity to irreparable mtDNA damage in fusion-deficient C. elegans remains unknown, one possibility is the existence of a threshold effect in which >65% of mtDNA must typically be damaged or lost prior to pathogenesis (Taylor and Turnbull 2005).…”
Section: Gene-environment Interactions: How Does Genetic Variationsupporting
confidence: 87%
“…AfB 1 , a foodborne mycotoxin and important carcinogen in the developing world, causes bulky DNA lesions when its epoxide metabolite reacts with DNA. We and others have found that AfB 1 preferentially, and irreparably (due to a lack of NER) damages mtDNA [15–17]. Arsenite, a global drinking water contaminant associated with the development of skin, lung, and bladder cancer, is a well-known inhibitor of several Krebs cycle dehydrogenases [48], ETC complexes [49], and is also capable of causing metabolic shifts from OXPHOS to aerobic glycolysis, otherwise known as the Warburg effect [36, 50].…”
Section: Resultsmentioning
confidence: 99%
“…We use 30 h of incubation time for all our experiments and encourage standardizing this time interval as starvation renders the animals more resistant to 6-OHDA treatment (González-Hunt et al , 2014; Offenburger et al , 2018b). After 30 h, several hundred L1s will accumulate in the wells, of which only around 200 will be used in the assay and only 50-100 randomly selected animals will be scored after treatment.…”
Section: Methodsmentioning
confidence: 99%